Diagnostic Pathology of Tumors of Peripheral Nerve. Issue 3 (16th February 2021) - Belakhoua, Sarra M; Rodriguez, Fausto J
Abstract: Neoplasms of the peripheral nervous system represent a heterogenous group with a wide spectrum of morphological features and biological potential. They range from benign and curable by complete excision (schwannoma and soft tissue perineurioma) to benign but potentially aggressive at the local level (plexiform neurofibroma) to the highly malignant (malignant peripheral nerve sheath tumors [MPNST]). In this review, we discuss the diagnostic and pathologic features of common peripheral nerve sheath tumors, particularly those that may be encountered in the intracranial compartment or in the spine and paraspinal region. The discussion will cover schwannoma, neurofibroma, atypical neurofibromatous neoplasms of uncertain biological potential, intraneural and soft tissue perineurioma, hybrid nerve sheath tumors, MPNST, and the recently renamed enigmatic tumor, malignant melanotic nerve sheath tumor, formerly referred to as melanotic schwannoma. We also discuss the diagnostic relevance of these neoplasms to specific genetic and familial syndromes of nerve, including neurofibromatosis 1, neurofibromatosis 2, and schwannomatosis. In addition, we discuss updates in our understanding of the molecular alterations that represent key drivers of these neoplasms, including neurofibromatosis type 1 and type 2, SMARCB1, LZTR1, and PRKAR1A loss, as well as the acquisition of CDKN2A/B mutations and alterations in the polycomb repressor complex members ( SUZ12 and EED ) in the malignant progression to MPNST. In summary, this review covers practical aspects of pathologic diagnosis with updates relevant to neurosurgical practice.